2018
DOI: 10.1073/pnas.1802749115
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic regeneration by relocalization of the Spemann organizer during twinning in Xenopus

Abstract: SignificanceMany animals, including humans, can generate identical twins from a single egg. We perfected a method by which a frog (Xenopus) egg cut in half along the dorsal–ventral (back to belly) axis at the 4,000-cell stage produced twins at high frequency. The large wound generated by bisection healed within an hour, juxtaposing cells that would normally form the most dorsal and ventral tissues in the intact embryo. Tracing the fate of microinjected cells showed that the dorsal Spemann organizer was formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…There have been few experimental systems, at least in arthropods, used for investigating these types of capabilities in embryonic fields [24][25][26]. Similar embryological phenomena have been reported in some vertebrate models [27]. P. tepidariorum offers an experimental system to study mechanisms of self-regulation.…”
Section: Self-regulationmentioning
confidence: 76%
“…There have been few experimental systems, at least in arthropods, used for investigating these types of capabilities in embryonic fields [24][25][26]. Similar embryological phenomena have been reported in some vertebrate models [27]. P. tepidariorum offers an experimental system to study mechanisms of self-regulation.…”
Section: Self-regulationmentioning
confidence: 76%
“…This has been accomplished mainly in amphibians, but also in fish, birds, and small mammals [ 37 , 38 , 39 , 40 ]. The organizer expresses numerous specific genes that encode transcription factors and secreted molecules, involved in complex regulatory pathways of the inducing activity of the organizer [ 7 ]. Some of the expressed transcription factors include Gsc (the first molecule expressed in the organizer to be discovered), Sia, dharma, Xtwn, Pintallavis, Xotx2, Xlim1, Xbra, Xanf1/HNF3-β, Lim1, and Xnot, which are homeodomain proteins [ 2 ].…”
Section: Overview Of Major Signaling Pathways and Targets Involved In Organizer-induced Embryonic Developmentmentioning
confidence: 99%
“…Third, the three germ layers will respond to the organizer’s signals [ 6 ]. Since the initial research carried out mainly by Spemann and Harland, in recent decades many experiments have been carried out to provide more knowledge about the function of the Spemann–Mangold organizer during embryonic development [ 3 , 5 , 7 , 8 , 9 , 10 ]. It has been found that the amphibious Spemann–Mangold organizer has developmental analogues in other vertebrates [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Embryos with the best D-V polarity (Klein, 1987) were selected at the 2-and 4-cell stages, cultured in 0.1 × Marc's modified Ringer's and staged (Nieuwkoop and Faber, 1967). Stage 8 embryos were manually dechorionated with watchmaker forceps and bisected with an eyelash knife in 0.3 × Modified Barth's Solution (MBS, Gurdon, 1976) as described by Moriyama and De Robertis (2018). Sagittal bisections cut the dorsal crescent in half, while dorsal and ventral halves were sectioned perpendicular to that plane.…”
Section: Embryo Manipulation and Generation Of Sagittal Half Embryosmentioning
confidence: 99%
“…The frequency of well-patterned twins was increased by choosing those embryos in which the large wound left by bisection was completed within 60 minutes, followed by a second screening for those sagittal half embryos in which the dorsal lip formed 90° away from the healing point. For stage 12 sagittally bisected embryos, a further selection was performed choosing half-embryos with asymmetric pigmentation on the left and right sides (see Moriyama and De Robertis, 2018).…”
Section: Embryo Manipulation and Generation Of Sagittal Half Embryosmentioning
confidence: 99%